NEUROPSYCHIATRIC ADVERSE EFFECTS OF ANTIBACTERIAL AGENTS - CYRIAC, SANTA TREASA; IYPE, DIVYA SARA (International Journal of Pharmacy and Pharmaceutical Sciences, 2021)
Anti-bacterial are agents that inhibit bacterial growth or kills bacteria and are a sub-type of antimicrobials. These are drugs used to treat infections, but they sometimes pose a threat of adverse events. Some of these adverse events are neuropsychiatric, which are generally hard to diagnose and is often paid less attention. They account for about 30% of total Adverse drug reactions (ADRs) caused by drugs in patients without mental abnormalities. The spectrum ranges from episodes of seizure to acute psychosis. The article emphasizes the frequency of such adverse events and means to raise awareness among medical practitioners regarding the same. The various neuropsychiatric adverse effects and the agents responsible have been reviewed, along with their possible mechanisms and general management. The information for writing this review was selected by searching for keywords such as Neurotoxicity, GABA, Psychosis, Naranjo scale, and Antibiomania in databases such as Google Scholar, PubMed, Elsevier, etc. After searching the articles in the above-mentioned databases, the articles were screened concerning their importance with our work and according to their title and abstract. Additional articles were discovered by checking the references in the current study's citations. Using this method, the various neuropsychiatric adverse effects of Antibacterial agents were summarized in this review.